1999
DOI: 10.1016/s0741-5214(99)70240-5
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral tomographic findings in patients undergoing carotid endarterectomy for asymptomatic carotid stenosis: short-term and long-term implications

Abstract: In our experience, preoperative SBI did not occur more frequently in the hemisphere ipsilateral to asymptomatic severe carotid stenosis. Although our study lacks a medically treated control group, our data show that SBI is predictive of poor neurologic outcome in asymptomatic patients undergoing CEA. We conclude that CT before CEA, selectively applied, provides information on long-term neurologic prognosis and that a less aggressive attitude towards CEA in asymptomatic patients with SBI may be justified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…Cao et al 4 analyzed late survival after CEA for asymptomatic lesions and correlated it to the presence of silent brain infarctions, with a 5-year survival of 86.0% without versus 78.3% with silent brain infarctions, and a 10-year survival of 69.3% versus 60.6%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cao et al 4 analyzed late survival after CEA for asymptomatic lesions and correlated it to the presence of silent brain infarctions, with a 5-year survival of 86.0% without versus 78.3% with silent brain infarctions, and a 10-year survival of 69.3% versus 60.6%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In one of the few studies of long-term survival after CEA for asymptomatic stenosis, Cao et al 4 found age Ͼ70 years, lacunar infarction, and diabetes to be independent predictors of late mortality. The correlation of diabetes with decreased late survival is in agreement with the present findings, and also with the results from a recent large review of patients having CEA, which included 64% with asymptomatic indication.…”
Section: Discussionmentioning
confidence: 99%
“…Silent infarctions are found in about a quarter of patients with asymptomatic carotid stenosis but do not consistently appear to be more common on the side of the carotid stenosis. [100][101][102][103] As with AF, data relating silent infarction to subsequent risk are limited but suggest greater risk of subsequent stroke and mortality among those with preoperative silent infarction. A systematic review and meta-analysis found 2 studies that showed that a nonlacunar pattern of cortical and subcortical silent CT infarctions ipsilateral to the carotid stenosis was associated with future stroke risk (pooled odds ratio [OR], 4.6; 95% confidence interval [CI], 3.0-7.2), but there were no prospective MRI studies linking silent infarction and stroke risk in this setting.…”
Section: Investigations For Patients With Silent Brain Infarctsmentioning
confidence: 99%
“…When both nonlacunar and lacunar CT-demonstrated brain lesions were present, the infarcts were classified as nonlacunar lesions. 34 All CT brain scans were reported by an experienced neuroradiologist (J.M.S.) who was unaware of patients' clinical characteristics.…”
Section: Ct-demonstrated Brain Infarct Classificationmentioning
confidence: 99%
“…50 Because of the association of asymptomatic hypoechoic plaques with nonlacunar silent CT-demonstrated brain infarcts shown in this study, it is tempting to implicate carotid atheroembolism as the pathogenetic factor for these types of infarcts. On the other hand, although the presence of CTdemonstrated brain infarcts may predict the development of ischemic stroke in patients presenting with transient ischemic attacks 51,52 and is associated with significantly worse prognosis after carotid endarterectomy, 34,53,54 their role as a risk factor for atheroembolic stroke in patients with asymptomatic carotid stenosis is not certain and remains to be proven.…”
Section: Sabetai Et Al Reproducibility Of Computer-quantified Carotidmentioning
confidence: 99%